Clinical relevance of Mycobacterium simiae in pulmonary samples - van Ingen, J; Boeree, M J; Dekhuijzen, P N R; van Soolingen, D (The European respiratory journal, 2008)
The aim of the present study was to determine the clinical relevance of Mycobacterium simiae isolation from clinical samples. The medical files of patients in the Netherlands from whom M. simiae was isolated between 1999 and 2006 were reviewed in order to assess frequency and clinical relevance. Clinical relevance was defined as fulfilment of the diagnostic criteria of the American Thoracic Society. From the files, 28 patients were identified, of whom six (21%) met the American Thoracic Society diagnostic criteria. A slight (54%) female predominance was observed, which is uncommon for nontuberculous mycobacteria isolation. Fulfilment of the diagnostic criteria and initiation of treatment were not in agreement; treatment results were poor. Only a minority of clinical M. simiae isolates are clinically relevant and, applying the American Thoracic Society diagnostic criteria, the number of true infections is overestimated. Physicians in the Netherlands do not always use these criteria in daily practice, resulting in both over- and underdiagnosis of M. simiae infection. Further studies are required in order to improve diagnostic criteria and treatment regimens.